(untitled) (Cambridge, UK,New York, 2004)
This volume is a review of up-to-date methods used in human growth research. Aimed at junior and senior researchers in human biology, anthropology, epidemiology and pediatrics involved in the analysis of normal and pathological growth and development data, it focuses on concepts, possibilities, limitations and applications
Keywords: Human growth,Human growth,Human growth,Sự phát triển loài người,Sự phát triển loài người; Research,Longitudinal studies,Statistical methods,Nghiên cứu,Phương pháp thống kê